2022
DOI: 10.1007/s10518-022-01464-2
|View full text |Cite
|
Sign up to set email alerts
|

Shaking table investigation of a low-cost and sustainable timber-based energy dissipation system with recentering ability

Abstract: SummaryThe aim of this paper is to demonstrate the efficiency of a low-cost and sustainable timber-based energy dissipation system with recentering ability, which can be used as a seismic isolation system or a tuned mass damper for the seismic protection of structures in developing or developed countries. The system, defined as Dovetail with SPrings (Dove-SP), utilizes the attractive properties of timber to store CO2, thus reducing the carbon footprint of the existing energy dissipation systems: It comprises t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In case the design requirements for the structure do not allow a residual sliding displacement or the weight of the structure does not allow the recentering by trucks, a recentering system that minimizes this residual sliding displacement has been proposed by ETH Zurich. Tsiavos et al [17] demonstrated through large-scale shaking table tests at ETH Zurich the efficiency of a low-cost and sustainable recentering system based on low-cost steel springs and deformable timber plates [18]. This system, which is based on a 'sandwich' seismic isolation strategy, can be used either as low-cost seismic isolation with recentering or a low-cost tuned mass damper, leading to residual sliding displacement lower than 5mm.…”
Section: Challenges Of Implementationmentioning
confidence: 99%
“…In case the design requirements for the structure do not allow a residual sliding displacement or the weight of the structure does not allow the recentering by trucks, a recentering system that minimizes this residual sliding displacement has been proposed by ETH Zurich. Tsiavos et al [17] demonstrated through large-scale shaking table tests at ETH Zurich the efficiency of a low-cost and sustainable recentering system based on low-cost steel springs and deformable timber plates [18]. This system, which is based on a 'sandwich' seismic isolation strategy, can be used either as low-cost seismic isolation with recentering or a low-cost tuned mass damper, leading to residual sliding displacement lower than 5mm.…”
Section: Challenges Of Implementationmentioning
confidence: 99%
“…It is desirable to use materials that are readily found in nature and have large reserves. Several types of materials have been tested and researched for GSI applications, including sand and gravel [15][16][17][18][19][20][21][22], sand-bitumen mixtures [23], EPS beads-sand mixtures [24], rubbersoil mixtures (RSMs) gravel-soil mixtures (GRMs) [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], geosynthetics [45][46][47][48], and geofoam [49][50][51][52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…The sliding displacement can be designed to occur within an acceptable range. This GSI mechanism is featured in two articles in this special issue (Banović et al 2022;Tsiavos et al 2022). 3.…”
mentioning
confidence: 99%
“…Amongst these, rubber-soil mixtures have been the most researched materials (Bernal-Sanchez et al 2023;Chiaro et al 2022;Dhanya et al 2023; Forcellini and Alzabeebee 2022; Nikitas and Bhattacharya 2023; Vratsikidis and Pitilakis 2022), whilst there is a case study with the use of whole waste tyres (Hazarika et al 2023). Meanwhile, other materials have also been investigated, including EPS beads (Edinçliler and Yildiz 2023), geosynthetics (Banović et al 2022;Dhanya et al 2023), stone pebbles (Banović et al 2022), sand, timber and PVC (Tsiavos et al 2022), polyurethane (Gatto et al 2022), super absorbent polymers (SAP) (Somma and Flora 2023), as well as various high-damping (Aloisio et al 2022) and low-modulus materials (Tsang 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation